Cost Analysis Of Type 2 Diabetes Mellitus Therapy In High-Income And Low And Middle-Income Countries: A Systematic Review - Raihana Nurul Izzah; Dwi Endarti; Tri Murti Andayani (Universitas Muhammadiyah Purwokerto, 2026)
Abstract Introduction: Diabetes is currently a very serious health problem. There is an increase in the prevalence and incidence of type 2 diabetes mellitus, this disease causes suffering for sufferers and also causes the death of a person, which makes a large economic burden for both the community and health care facilities. This study aimed to analyze the total direct medical costs of type 2 diabetes mellitus therapy in high-income, low- and middle-income countries. Methods: A systematic review was carried out following the PRISMA guidelines. The article search method was carried out by searching PubMed, ScienceDirect, and Springer for articles that analyzed the total direct medical costs of type 2 diabetes mellitus therapy. Nine articles are considered important to be discussed in this review, these nine articles were published between January 2014 and December 2023. Result: The results showed that the two components that had the greatest impact on the direct medical costs of managing type 2 diabetes were inpatient services and medications. Direct medical costs ranged from the lowest to the highest at 343,93 for the Kenya study to 5.090,48 for the Spain study, while medication costs ranged from 34,23 for Indonesia to 645,52 for Bangladesh from the average annual direct costs per person. The most widely used drugs were oral hypoglycemic drugs, while the most expensive drugs were Combination of Oral and Insulin. Complications of diabetes resulted in increased expenditure of the total direct medical costs. Conclusion: This review concludes that the studies reviewed indicate a considerable health financing burden in the care of type 2 diabetes mellitus. Efforts to prevent diabetes complications have the possibility of saving the cost of diabetes care.